Minimally Invasive Treatments of Hemorrhoidal Disease - Ahmad Izadpanah (Shiraz University of Medical Sciences, 2013)
Context Minimally invasive procedures are used for treatment of nonresponsive hemorrhoids to conservative therapy. These OPD (Out-Patient Department) procedures are effective to eradicate the hemorrhoid symptoms with minimal postoperative pain and complications. Evidence Acquisition In this review, PubMed, and MEDLINE were searched with a time limitation (2002- 2012). Recent articles in English journals were reviewed to evaluate and compare these minimally invasive procedures including Rubber band ligation (RBL), Infrared coagulation (IRC), Direct current Electrotherapy (DCE), and Sclerotherapy. Results Upon the articles, 881 were treated with RBL, 454 with IRC, 1203 with DCE, and 2372 with sclerotherapy. Postoperative pain, which is a common complication of hemorrhoidectomy, was 3-25% in RBL, 2.13-4.3% in DCE, and 1.8-7% in sclerotherapy. Pain was mild to moderate and rarely needed analgesic. Postoperative rectal bleeding was seen in 1.26-32.4% of patients treated with RBL. Recurrence of preoperative symptoms was 1.9-39% for RBL, 6.9-21% for sclerotherapy, and 2.9-3% for DCE. Postoperative complications were minor in all procedures and for sclerotherapy it was seen in 6.9-21% of patients. Success rate was 69.4-96.4% in RBL, 80% in IRC, 89.3-99.7% in sclerotherapy, and 98.2% in DCE. Patients’ satisfaction was 98% for DCE versus 99% for RBL and IRC. Operation time for each tag of hemorrhoid was 4.5-10 minutes for DCE, regarding different amplitudes of currency and degrees of hemorrhoid, and 13 minutes for sclerotherapy and not reported for other methods. Conclusions Minimally invasive procedures are used depending on surgeon’s experience and preference. These modalities are comparable from different aspects. The cost of treatment and availability of equipment may affect the choice of modality. All of these techniques could be used in patients resulting in maximum success rate and minimum complications.